2019
DOI: 10.18510/hssr.2018.637
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Affecting Traditional Fishermen in Maintaining the Resilience of Marine Areas in the Context of Indonesian State Defense

Abstract: Purpose of the study: The purpose of this study is to empirically examine the factors that influence traditional fishermen in maintaining the resilience of marine areas in order to defend the country and examine the model of causality relationships that are formed as well as the influence of causality between these variables. Methodology: The study was conducted in the Depok coastal area, Bantul - Yogyakarta with traditional fishermen as the respondents who are members of the Mina Bahari Fishermen Cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Several previous studies have shown that improving the quality of efforts in the form of fishing facilities will increase the ability to optimize the management of natural resources for capture fisheries (Rivai et al 2017;Yoshioka et al 2019;Sabihaini et al 2018).…”
Section: B the Impact Of Detrimental Capital Assistance Systems In Coastal Communitiesmentioning
confidence: 99%
“…Several previous studies have shown that improving the quality of efforts in the form of fishing facilities will increase the ability to optimize the management of natural resources for capture fisheries (Rivai et al 2017;Yoshioka et al 2019;Sabihaini et al 2018).…”
Section: B the Impact Of Detrimental Capital Assistance Systems In Coastal Communitiesmentioning
confidence: 99%
“…Statistical data indicate that the development of poverty in Bengkulu Utara Regency has a declining trend, although it moves slowly (graphically, this trend can be seen in Figure 1) (Badan Pusat Statistik Provinsi Bengkulu, 2020). Other information indicates that most of the marine natural resources produced are sourced from small fishermen/traditional fishermen (Sabihaini et al, 2018). The factual/empirical conditions (Das Sein) are shown by the contradictory phenomenon of poverty in the Bengkulu Utara Regency (the contradiction between the still high poverty rate and the declining trend of poverty) (shown by Figure…”
Section: Introductionmentioning
confidence: 99%